Stosunek św. Ambrożego w "De Nabuthae" do własności i jałmużny - Pankiewicz, Ryszard (Vox Patrum, 1986)
Saint Ambrose’s life is an excellent example of the activity of a man associated with church during great change concerning not only socio-political history of the Mediterranean world but also the ways of thinking.